Justification of Technical System Control in Developing and Testing Objects of Missile and Space Technology - A. A. Fedorovskiy (Nauka i Obrazovanie, 2015)
Tests in general lifecycle of missile and space technology, play a special role. The high cost of such products and a little time for creation and refinement, allow only a limited number of tests. Justification of the appropriate number of tests and finding the ways to reduce it are important from the practical point of view. When the appropriate number of field tests is impossible to implement, as well as if full or partial realization of the sample operation conditions is impossible the authors propose to use software with the involvement of previously obtained aprioristic information to have the modeling results of the functioning sample or its parts, according to the reliability and quality standards. Involvement of statistical methods for systems and objects of the missile and space equipment is limited to the single number of the carried-out tests. Currently used models and methods for systems of missile and barreled weapon do not allow us to conduct analysis and provide guidance on emerging issues of concern to ensure the quality and reliability of objects of the missile and space equipment by results of tests. The method of probabilistic and statistical analysis of the stochastic system operability is supposed to be used to solve a problem of the planning tests, assessment and control of reliability of technical systems at tests using aprioristic calculated and experimental information. This method makes it possible to relate the number of tests, required to prove the desirable level of reliability, to different types of constructional, functional, structural reserves of the system, as well as the level of information-and-measuring base and the completeness of available information. Thus, the structure of controlled elements, their importance, and acceptance conditions including elaboration of actions and recommendations to eliminate discrepancies in controlled parameters and improve quality of the considered system are justified and formed when solving a problem of the planning tests.